Evaluation of skin patch matrix of the lyophilized ethanolic extract from the leaves of Mentha arvensis Linn. - Balanay, Rua Marie F.​; Pascua, Rikki Sychar Rose M.​; Velez, Vida Valerie V.​; Balotro, Bienvenido S.​ (Manila: Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines Manila, 2018.)
In this study, the ethanolic extract of Mentha arvensis Linn leaves was used in the formulation of skin matrix patch. The lyophilized extract was subjected to air and thermal stability testing, and compatibility testing with different excipients prior to formulation of the topical patch matrices. The organoleptic characteristics and quality control parameters of the formulated patches were evaluated. Trial formulations with satisfactory results were obtained and assessed for their drug release profile. The release profile of trial formulations 1 and 2 were best fitted into zero-order kinetic model. An independent-samples t-test was conducted to compare the release profile of the trial formulations. There was no significant difference in percent amount of active substance released from trial to formulations 1 and 2, which indicates that different polymer to plasticizer ratios of hydroxypropyl methylcellulose/methyl cullulose and dibutyl pthalate, does not affect the release of active substance from the topical patches.
Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines Manila, June 2018.
Keywords: Mints (Plants); Plant extracts; Yerba Buena